Peran Organizational Citizenship Behavior sebagai Mediator Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan - Thoyib, Armanu; Sukmawati; Surachman (Universitas Brawijaya, Indonesia, 2013)
The objejective of this research to study the role of organizational citizenship behavior as media tor for the impact of job satisfaction, job environment and organizational commitment towards employee performance. The research perform with explanatory research was carried out in the food and beverage manufacture industry in the municipality of Makassar. The research sample about 200 respondents of total 857 member of population in the division of production, taken by proportional random sampling. Data was analyzed by The structural equation model (SEM). The result indicated that: (1) job satisfaction has significant impact on organizational citizenship behavior, (2) job environment has significant impact on organizational citizenship behavior, (3) organizational commitment has significant impact on organizational citizenship behavior, (4) job satisfaction has significant impact on employee performance, (5) job environment has significant impact on employee performance, (6) organizational commitment has significant impact on employee performance, and (7) organizational citizenship behavior has significant impact on employee performance.